(untitled) (Damascus University Journal of agriculture sciences, 2021)
The study has done in UN laboratory in Darra for study the chemical ,physical characterization some kinds of Honey in Syria, samples have been collected from the Syrian honey during 2019 differ each other in the pasture type , (Mountain honey, source:Salkhad and Shahbaa in Sweedaa where apple and almond are spread), (Zalou honey, source: Talkalah and Alhwash in Homs), (Al-Kena honey, source:Jeleen and Abdeen in Darra), (Citrus honey, source:Jabla and Alhefa in Lattakia where lemon and orange are spread) , (Al-Shawkeat honey, source:Saasaa and kanaker in Damascus Country where silybum and eryngium are spread). Results reveal that mountain honey was low in moisture(15.72%), Zalou honey was(16.33%), high in ash (0.38%) in mountain honey, high in total acids(15.90 meq/Kg) in citrus honey, and low in total acids (7.31 meq/Kg) in kena honey ,HPLC analysis of sugar showed high fructose(44.2%), high maltose(5.5%)in mountain honey, and low in fructose (36.3%), maltose (3.8%) in shawkeat honey, total phenoles was the highest value (14.62 mg/100g) in mountain honey, and the lowest value (11.2mg/100g) in kena honey, so there is an affect of pasture type on chemical, physical characterization of honey.